A Simonffy utcától az Egyetem térig: az egyetemi könyvtár első évtizedei - Virágos, Márta (Gerundium, 2016)
From Simonffy Street to University Square: the First Decades of Debrecen’s University Library. The University and National Library of the University of Debrecen celebrated the centennial of its foundation on the last day of September, 2016. The institution, which boasts the second largest deposit collection in the country, emerges from the system on account of its unique national services, as well as of its extraordinary priceless collection. Several components of this valuable collection still await careful exploration for the purposes of promoting scientific and scholarly activity, as well as of ensuring the possibilities of access for the general public. The present study highlights the stages of the initial placement of the university library and its subsequent relocation in the University’s main academic building.